Monthly Patterns of Ammonia Over the Contiguous United States at 2‐km Resolution. Issue 5 (8th March 2021) - Wang, Rui; Guo, Xuehui; Pan, Da; Kelly, James T.; Bash, Jesse O.; Sun, Kang; Paulot, Fabien; Clarisse, Lieven; Van Damme, Martin; Whitburn, Simon; Coheur, Pierre‐François; Clerbaux, Cathy; et al.
Abstract: Monthly, high‐resolution (∼2 km) ammonia (NH3 ) column maps from the Infrared Atmospheric Sounding Interferometer (IASI) were developed across the contiguous United States and adjacent areas. Ammonia hotspots (95th percentile of the column distribution) were highly localized with a characteristic length scale of 12 km and median area of 152 km 2 . Five seasonality clusters were identified with k‐means++ clustering. The Midwest and eastern United States had a broad, spring maximum of NH3 (67% of hotspots in this cluster). The western United States, in contrast, showed a narrower midsummer peak (32% of hotspots). IASI spatiotemporal clustering was consistent with those from the Ammonia Monitoring Network. CMAQ and GFDL‐AM3 modeled NH3 columns have some success replicating the seasonal patterns but did not capture the regional differences. The high spatial‐resolution monthly NH3 maps serve as a constraint for model simulations and as a guide for the placement of future, ground‐based network sites. Plain Language Summary: Ammonia (NH3 ) contributes to the formation of particulate matter, which is known to degrade air quality and human health. The major source of NH3 is from agricultural activities, yet observational constraints on NH3 are limited, particularly at both monthly resolution and high spatial resolution. We have developed high spatial resolution (2 km) satellite maps of NH3 on a monthly scale in the United States. Areas with the highest NH3 are generally very localized with typical length scales of ∼12 km. The seasonal patterns varied dramatically based upon the underlying agricultural activities. These high‐resolution satellite maps can be used as observational constraints on the seasonalities and spatial patterns for modeling of atmospheric NH3 . Key Points: High spatial resolution (2 km) maps of NH3 show that hotspots are highly localized with characteristic length scales of ∼12 km Large monthly variations of NH3 columns are observed with different seasonality patterns by region and type of agricultural activities Satellite NH3 maps provide insights for future ground‐based observational networks and constraints for model NH3 spatiotemporal patterns